2010
DOI: 10.1002/ps.1978
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of resistance to spirodiclofen and five other acaricides in Panonychus citri collected from Chinese citrus orchards

Abstract: Great variations in resistance to the tested acaricides were observed among the sampled populations. The Pinghe population developed resistance to all the acaricides tested. The Jianning population was susceptible to most acaricides tested, except pyridaben. Resistance management strategies were conducted on the basis of these observations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
83
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(90 citation statements)
references
References 9 publications
4
83
0
3
Order By: Relevance
“…However, several field populations of P. citri have already developed high levels of pyridaben resistance in spite of its short term use (Hu et al 2010). Synergistic experiments suggest that GSTs have a major role in pyridaben resistance in P. citri (Meng et al 2000;Liu et al 2010).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…However, several field populations of P. citri have already developed high levels of pyridaben resistance in spite of its short term use (Hu et al 2010). Synergistic experiments suggest that GSTs have a major role in pyridaben resistance in P. citri (Meng et al 2000;Liu et al 2010).…”
Section: Discussionmentioning
confidence: 96%
“…Since the first acaricide resistance was reported in China in 1979, over the following decades citrus red mites have developed resistance to dicofol, pyrethroids, organotin miticide, hexythiazox, spirotetramat, amitraz, propargite, diafenthiuron, abamectin, mitochondrial electron transport inhibitor (METI) acaricides and spirodiclofen (Huang 1979;Ran et al 2009;Hu et al 2010), but the studies to identify the biochemical mechanisms were carried out just in a few cases Ran et al 2009;Niu et al 2011). Despite reliance on acaricides for control of P. citri, detoxification in these species is poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Demaeght et al (2013) 680 kat spirodiclofen dirençli T. urticae popülasyonunun aynı grupta yer alan spiromesifen ve spirotetramat akarisitlerine karşı da çapraz direnç geliştirebileceğini bildirmişlerdir. Hu et al (2010) 90.8 kat spirodiclofen dirençli Panonychus ulmi (Acari:Tetranychidae) popülasyonunda spirotetramat'a karşı çapraz direnç belirlemişlerdir. Spirodiclofen ve spiromesifen etken maddeleri tetronik asit türevi grubu altında yer alan ve etki mekanizmaları benzer akarisitlerdir.…”
Section: Tetranychus Urticae Populasyonlarının Esteraz Glutathion S-unclassified
“…The authors found the profile of biological activity and symptomology of poisoning of this compound similar to those previously described for spirodiclofen and spiromesifen. On the other hand, in two recent studies dealing with spirodiclofen resistance, the data on toxicity of spirotetramat to larvae of susceptible and resistant strains of Panonychus citri (Hu et al, 2010) and P. ulmi (Kramer and Nauen, 2011) were presented.…”
Section: Biological Activity and Mode Of Actionmentioning
confidence: 99%
“…Hu et al (2010) investigated spirodiclofen susceptibility in P. citri populations collected from citrus orchards at six locations in China and found high resistance ratios (RR) in two populations (RR=50 and 90.8). These two populations also showed various levels of resistance to other acaricides used in P. citri control, as well as moderate cross-resistance to spirotetramat (RR=16.9 and 22.4), which was not present on Chinese market at the time.…”
Section: Resistance and Cross-resistancementioning
confidence: 99%